Transcranial Static Magnetic Field Stimulation of the Motor Cortex in Children - Hollis, Asha; Zewdie, Ephrem; Nettel-Aguirre, Alberto; Hilderley, Alicia; Kuo, Hsing-Ching; Carlson, Helen L.; Kirton, Adam (Frontiers in Neuroscience, 2020)
Background: Non-invasive neuromodulation is an emerging therapy for children with early brain injury but is difficult to apply to preschoolers when windows of developmental plasticity are optimal. Transcranial static magnetic field stimulation (tSMS) decreases primary motor cortex (M1) excitability in adults but effects on the developing brain are unstudied. Objective/Hypothesis: We aimed to determine the effects of tSMS on cortical excitability and motor learning in healthy children. We hypothesized that tSMS over right M1 would reduce cortical excitability and inhibit contralateral motor learning. Methods: This randomized, sham-controlled, double-blinded, three-arm, cross-over trial enrolled 24 healthy children aged 10-18 years. Transcranial Magnetic Stimulation (TMS) assessed cortical excitability via motor-evoked potential (MEP) amplitude. Motor learning was assessed via the Purdue Pegboard Test (PPT). A tSMS magnet (S-45-30-N, Supermagnete) or sham was held over left or right M1 for 30 minutes while participants trained the left hand. A linear mixed effect model was used to examine intervention effects. Results: All 72 tSMS sessions were well tolerated without serious adverse effects. Neither cortical excitability as measured by MEPs nor paired-pulse intracortical neurophysiology was altered by tSMS. Contralateral tSMS inhibited early motor learning in the trained hand (p<0.01). Later in the motor learning process, ipsilateral tSMS facilitated motor learning (p<0.01). Conclusions: tSMS over M1 can modulate motor learning in children, with effects specific to side and stage of learning. Unlike adults, tSMS did not produce measurable changes in MEP amplitude. Our findings suggest therapeutic potential for tSMS neuromodulation in young children with cerebral palsy (CP).